Analysis of the current situation and trends in the field of innovative development of Russia’s regional economic systems - S. Ye. Afonin (Вестник университета)
The relevance of the study is conditioned by such directions, which in the last few years have a signiﬁcant impact on the level of innovative development of regional socio-economic systems, as well as the need for analysis, which allows timely identiﬁcation of factors that negatively affect regional systems. The level of uneven development of the constituent entities of the Russian Federation has been assessed, considering historical traditions, which have a signiﬁcant impact on economic potential and interrelations with international communities in the context of the regional policy of the state. In this regard, the topic of the study is aimed at analyzing the current situation and trends in the ﬁeld of innovative development of Russia’s regional economic systems. The essence of the conducted research is reduced to the study of materials of economists who considered the ways and mechanisms of analysis of the current situation and trends in the ﬁeld of innovative development of the country’s regional economic systems, considering the level of development of the constituent entities’ economy, which in recent years is modernizing even in the conditions of severe restrictions and imposed sanctions. The regional socio-economic systems and various methods of its realization have been assessed.